Dinamika Resiliensi Pada Orangtua Yang Memiliki Anak Autis Berprestasi - Anjari, Niza, Setia Asyanti, S.Psi, M.Si (2016)
The purpose of this study was to describe the dynamics of the resilience of parents of children with autism excel. Researchers used descriptive qualitative approach with three key informants and informant support 3. Mechanical election informant in this research is purposive sampling, based on the characteristics that parents who have children with autism excel and close to children with autism. Data were collected through semi-structured interviews and analyzed thematically. Analytical results from this study indicate that parents of children with autism have problems including a lack of knowledge about autism, stress, time consumed a lot and economic constraints. The dynamics of resilience that successfully revealed in this study, among other things oangtua experiencing feelings of distress such as stress and despair, then parents feel jealous of other parents who have normal children so emotions uncontrolled (feelings and behavior negative), but the parents began to accept state by being patient and calm for family support (recovery phase). Then parents began rapidly developing States to strive, think positively and to optimize the potential of children and eternally grateful to Allah SWT. Of patience and diligence of parents can develop the potential in autistic children to earn achievements.